Labour Market Success of Engineering Graduates - Kiss, Zsuzsanna; Barizsné Hadházi , Edit (International Journal of Engineering and Management Sciences, 2016)
The study aims to explore the labor market success of engineering graduates. The role of science field in the areas of job search time, earnings and job congruence proved significant. The engineering discipline proved to be outstanding in all the tree tested indicators. The database was GraduatesTracking System 2011-2012 (DPR 2011-2012). The indicators of employ ability could be compared among the young graduates of domestic higher education institutions in the engineering science, and similarities and differences could be highlighted